Quantifying patterns of the power generation sector's low-carbon transition using machine learning and asset-level datasets - Alova-Beitner, G (2021)
The past decades have seen a dramatic decline in the costs of clean power generation, driven by support policies and technology improvements, making renewable energy increasingly more cost-competitive. Yet, the share of solar and wind in global generation mix remains low, with fossil fuels continuing to dominate. This points to potential frictions in the electricity sector’s transition to renewables and, even more so, in the sector’s shift away from fossil fuels. Key research gaps lie in understanding and accurately capturing the pace and nature of the on-going low-carbon transition of the power sector, both at the company and country level, and across different geographies. While developing countries merit a particular research focus, given the dual challenges they face to simultaneously industrialise and decarbonise their economies, extant research tends to be often limited to the Western world and single-country studies. In this context, there is a particular need for large international analyses to examine the intricate interrelationships of different factors affecting the decarbonisation patterns of the power sector across companies and countries.